2019
DOI: 10.1590/s1984-29612019048
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma scalpturatum Neumann, 1906 (Acari: Ixodidae): confirmation in Acre State, Brazil, and description of parasitism in a human

Abstract: Amblyomma scalpturatum is a tick species that is unique to South America. It is commonly associated with the Amazon biome and has been reported in some Brazilian states. This tick species exhibits host specificity: it parasitizes tapirs and suidae. Its role in transmitting pathogens to humans is still unknown. Amblyomma scalpturatum is known to be a human-biting tick; however, there is only one report showing that humans make suitable hosts for this species. The knowledge of tick fauna is lacking in the Acre S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In that study, three genera of ticks were identified parasitizing the animals, totaling eight species: Amblyomma dubitatum Neumann, 1899, Amblyomma naponense Packard, 1869, Amblyomma humerale Koch, 1844, Amblyomma pacae Aragão, 1911, Amblyomma rotundatum Koch, 1844, Amblyomma varium Koch, 1844, R. microplus, and Dermacentor nitens Neumann, 1897. More recently, the presence of Amblyomma scalpturatum Neumann 1906, collected in situ, and its parasitism on a human host were confirmed in the state of Acre (Aguirre et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In that study, three genera of ticks were identified parasitizing the animals, totaling eight species: Amblyomma dubitatum Neumann, 1899, Amblyomma naponense Packard, 1869, Amblyomma humerale Koch, 1844, Amblyomma pacae Aragão, 1911, Amblyomma rotundatum Koch, 1844, Amblyomma varium Koch, 1844, R. microplus, and Dermacentor nitens Neumann, 1897. More recently, the presence of Amblyomma scalpturatum Neumann 1906, collected in situ, and its parasitism on a human host were confirmed in the state of Acre (Aguirre et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…The genus Amblyomma is the most common in the Amazon Biome (Gianizella, Moraes, Nascimento, & Martins, 2018b). Ticks of this genus have already been observed parasitizing different groups of animals in the Amazon: wild birds (Ogrzewalska, Uezu, & Labruna, 2010;Martins, Fecchio, & Labruna, 2014;Lima et al, 2018), chelonians (Labruna, Camargo, Terrassini, Schumaker, & Camargo, 2002;Soares et al, 2015;Gianizella et al, 2018b), crocodilians (Labruna et al, 2005;Witter et al, 2016;Gianizella et al, 2018a), wild mammals (Martins et al, 2013;Soares et al, 2015), and even the human being (Aguirre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human parasitism by the nymphal and adult stages of this species has been reported in the states of Mato Grosso (municipality of Jauru) and Rondônia (municipality not precisely indicated), however in this latter state it was not specified whether these adult ticks were fixed or walking on humans [38,93]. The nymphal stage was also collected from a human who was probably infested with this tick in the municipality of Porto Velho in the state of Rondônia [115]. The nymph and adult stages of this species were also found parasitizing humans in the state of Amazonas, in the municipalities of Coari, Fonte Boa, Jutaí, Presidente Figueiredo and Santa Isabel Rio Negro [31,107].…”
Section: Hard Ticks Associate With Humansmentioning
confidence: 99%
“…As so, A. incisum had only been reported once, by Aragão (1936), through examining the material in the Ixodid Collection of the Oswaldo Cruz Institute. About A. scalpturatum was confirmed by Aguirre et al (2019) through morphological and molecular analyses (subjected to sequencing of the ITS2 gene). Now, through the present study, occurrence of the species A. latepunctatum in the state of Acre has been confirmed.…”
Section: Introductionmentioning
confidence: 99%